Electronic identity - Andrade, Norberto Nuno Gomes (SpringerBriefs in Cybersecurity,, 2014)
With the increasing availability of electronic services, security and a reliable means by which identity is verified is essential. Written by Norberto Andrade the first chapter of this book provides an overview of the main legal and regulatory aspects regarding electronic identity in Europe and assesses the importance of electronic identity for administration (public), business (private) and, above all, citizens. It also highlights the role of eID as a key enabler of the economy. In the second chapter Lisha Chen-Wilson, David Argles, Michele Schiano di Zenise and Gary Wills discuss the user-centric eCertificate system aimed at supporting the eID system. Electronic Identity is essential reading for researchers, lawyers, policy makers, technologists and anyone wishing to understand the challenges of a pan-European eID.